2014
DOI: 10.2215/cjn.05040513
|View full text |Cite
|
Sign up to set email alerts
|

Renal Flare as a Predictor of Incident and Progressive CKD in Patients with Lupus Nephritis

Abstract: SummaryBackground and objectives Renal flares are common in lupus nephritis. The impact of flares on the development of CKD in lupus nephritis was examined.Design, setting, participants, & measurements A retrospective analysis of prospectively collected data from the Ohio Systemic Lupus Erythematosus (SLE) Study was conducted to determine if renal flares predispose to new CKD or progression of preexisting CKD. Patients in the Ohio SLE Study were followed from 2001 to 2009, with a median follow-up of 6 years. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 13 publications
3
82
0
Order By: Relevance
“…Renal flares increase cumulative injury to the renal parenchyma, thus increasing the likelihood of chronic damage. The Ohio SLE study found that renal flare for more than 30% of the follow‐up duration was independently associated with developing new or progressive CKD (odds ratio 20, 95% confidence interval 4.6–91.3) . It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant‐related complications such as infections …”
Section: Discussionmentioning
confidence: 99%
“…Renal flares increase cumulative injury to the renal parenchyma, thus increasing the likelihood of chronic damage. The Ohio SLE study found that renal flare for more than 30% of the follow‐up duration was independently associated with developing new or progressive CKD (odds ratio 20, 95% confidence interval 4.6–91.3) . It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant‐related complications such as infections …”
Section: Discussionmentioning
confidence: 99%
“…For example, kidney biopsies after induction therapy with high-dose corticosteroids and cyclophosphamide or MMF generally show an increase in chronic damage, even in those patients who achieved a complete clinical remission to induction alone (57). LN flare is also an important risk factor for CKD and CKD progression (76) and flares may occur in 25% of patients (77,78). These outcome statistics suggest there is considerable room for improvement in the treatment of LN.…”
Section: The Treatment Of Ln Management Strategymentioning
confidence: 99%
“…Proteinuria induces structural and functional changes in different kidney cells; with more protein traffic to the proximal/distal collecting ducts and subsequent inflammation and fibrosis, and progressive loss of kidney function [45]. Proteinuria produces active glomerular inflammation and can be considered a manifestation of an Acute Kidney Injury (AKI), which is a recognized risk factor for CKD [46]. Touma et al, demonstrated that proteinuria is a marker for the long term prognosis of kidney function [47].…”
Section: Proteinuria In Lupus As a Prognostic Factor For Renal Outcomesmentioning
confidence: 99%
“…In SLE, nephritic and proteinuric flares (with increase in 24H-P>1.0 g/day) of LN contribute equally to poor kidney outcomes [46], with heavy proteinuria resulting in a higher risk for CKD and end stage CKD with requirement for dialysis [57]. Fiehn et al, compared the renal prognosis of patients with LN in 2 groups: from 1980-1989 (group 1) and 1990-2000 (group 2), showing less histological signs of chronicity and proteinuria for group 2.…”
Section: Proteinuria In Lupus As a Prognostic Factor For Renal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation